Permeability characteristics and structural evolution of compacted loess under different dry densities and wetting-drying cycles. - Kang-Ze Yuan; Wan-Kui Ni; Xiang-Fei Lü; Xi-Jun Wang (PLoS ONE, 2021)
Permeability characteristics of compacted loess is always an important topic in soil mechanics and geotechnical engineering. This study explored the permeability characteristics of compacted loess under different dry densities and wetting-drying cycles, and found that as the dry density increases, the compacted loess surface became denser, the saturation permeability coefficient and saturation infiltration rate decreased. However, the wetting-drying cycle presented the opposite result. Meanwhile, the evolution of the microstructure was investigated by Scanning Electron Microscope (SEM) and Nuclear Magnetic Resonance (NMR) to explain the change of its permeability characteristics. The size of compacted loess aggregates was quantitatively analyzed by Image-Pro Plus (IPP) software. It showed that the size of compacted loess aggregates for different dry densities were concentrated from 10-100 μm, occupying 65.0%, 58.19%, and 51.64% of the total aggregates area respectively. And the interesting finding was that the area occupied by 10-50 μm aggregates remained basically unchanged with the number of wetting-drying cycles increasing. Therefore, the size of 10-50 μm aggregates represented the transition zone of compacted loess. NMR analyses revealed that with increasing dry density, the volume of macropores in the compacted loess rapidly decreased, the volume of mesopores and small pores increased. Meanwhile, the change in micropores was relatively small. The pore volume of the compacted loess after three wetting-drying cycles increased by 8.56%, 8.61%, and 6.15%, respectively. The proportion of macropores in the total pore volume shows the most drastic change. Variations in aggregate size and connection relationships made it easier to form overhead structures between aggregates, and the increased of macropore volume will form more water channels. Therefore, the change in permeability characteristics of compacted loess is determined by aggregate size, loess surface morphology, and the total pore volume occupied by macropores.